Controls of Wind-Driven Jet on the Distribution of Pelagic Cnidarians in the Midwestern South China Sea - Ge, Ruping; Chen, Hongju; Li, Ling; Liu, Guangxing; Huang, Bangqin; Wang, Lisha; Zhuang, Yunyun; Liu, Xin (Frontiers in Marine Science, 2021)
The coastal water transported by the combined action of southwest wind jet and anticyclonic eddy substantially influences the biological processes in the midwestern South China Sea. However, how the wind-driven jet affects the zooplankton community remains unclear. In this study, the species number, abundance, and vertical distribution of medusae were investigated in the wind-driven jet (WJR) and non-wind-driven jet regions (NWJR). The low-salinity and nutrient-rich coastal water substantially influenced species composition, abundance, and vertical distribution of medusae in the WJR. The species number of the meroplanktonic hydromedusae in the WJR was approximately twice that in the NWJR due to the horizontal transport of wind-driven jets. The abundances of holoplanktonic hydromedusae in WJR were 38.2 ± 9.3 ind⋅m–3, which were thrice of that in the NWJR regions, caused by the abundant diet in the WJR. Additionally, only the abundance of medusae above the thermocline was affected by the coastal water in WJR, while these showed no significant difference below the thermocline between the WJR and the NWJR. Generalized additive model analyses suggested that the diet was the most important factor affecting the abundance of the holoplanktonic hydromedusae and siphonophore, whereas meroplanktonic hydromedusae were influenced by the combination of temperature, salinity, and diet.